Development of accreditation modules based on hospital types in Iran: Protocol for a mixed methods study - Ali Ghaffarian; Azam Cheraghi; Masoud Ferdosi (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Among different tools, accreditation is widely used worldwide to improve the quality and safety of hospital services. In Iran, as in many other countries, the same accreditation standards apply to all hospitals, regardless of their size and type of activity. This has given rise to many problems for hospitals. MATERIALS AND METHODS: We will conduct this study in three phases: In the first phase, relevant individuals are interviewed to identify challenges caused to hospitals by applying the same standards for all types of hospitals and clarify issues that could be removed or changed in small hospitals. In the second phase, a scoping review is conducted on the literature about accreditation models worldwide. The first and second phases are conducted simultaneously, and a new accreditation model for Iran hospitals is derived by combining their results. In the final phase, using the Delphi technique, the obtained model and accreditation modules are verified during Delphi rounds. DISCUSSION: A more appropriate accreditation model that matches the characteristics of the target hospitals could be the output of this study. It is expected that the model could improve the process of evaluating the quality of hospital services through the accreditation tool.